1962
DOI: 10.1111/j.1365-2621.1962.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Some Subcellular Fractions from Seeds of Arachis hypogaeaa

Abstract: SUMMARY Five fractions of parenchymatous cells of the cotyledon of the peanut were isolated by homogenization and differential centrifugation from nonaqueous media. These are two protein‐rich fractions (one of which appears to be aleurone grains), starch grains, a fines material, and cell wall fragments. In addition, a fraction composed largely of vascular tissue of the cotyledon was isolated. The nitrogen of the cell is concentrated in the two protein‐rich fractions, phytin in the aleurone grains, sucrose mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 20 publications
5
23
0
Order By: Relevance
“…This confirms the results of Dieckert et al (8) who found that the same proteins exist in different aleurone preparations separated by differential and density-gradient centrifugation. However, the presence of 1 antigen in the large aleurone fraction, which is not present in the small aleurone fraction could signify a' difference between these 2 particles or could simpfWi originate from contamination by the nuclei.…”
Section: Resultssupporting
confidence: 82%
“…This confirms the results of Dieckert et al (8) who found that the same proteins exist in different aleurone preparations separated by differential and density-gradient centrifugation. However, the presence of 1 antigen in the large aleurone fraction, which is not present in the small aleurone fraction could signify a' difference between these 2 particles or could simpfWi originate from contamination by the nuclei.…”
Section: Resultssupporting
confidence: 82%
“…Therefore, it seems probable that the role of metalloproteinases is to initiate the enzymatic proteolysis of storage proteins. By contrast, in legume seeds where most protein bodies lack globoids (Pernollet 1978;Sobolev 1985) and the amount of phytin in these organelles in considerably lower (Dieckert et al 1962;Sobolev et al 1976), cysteine proteinases, synthesized de novo, appear to act as the starting enzymes for storage-protein proteolysis (Bewley and Black 1985;Shutov and Vaintraub 1987).…”
Section: Discussionmentioning
confidence: 99%
“…23 ) RNA was determined by the methods of Kirby24) and Dieckert et a1. 25 ) Lipid analysis. Lipids extracted from the subcellular fractions were analyzed by thin-layer chromatography.…”
Section: Methodsmentioning
confidence: 99%